Puberty in ewes - Monteiro, Claudia Dias; Bicudo, Sony Dimas; Toma, Hugo Shisei (Pubvet, 2015)
Ewes present a model of seasonal reproduction with incidence of estrous cycles concentrated during the autumn and winter. One of the main responsible factors for that characteristic is the photoperiod. There are several definitions as for the beginning of the puberty, as: age to the first estrus, age to the first ovulation and age in which the female supports the pregnancy without future harmful effects. In ewes this age is between 4 and 14 months. Close to the first ovulation, increase is verified in the pulsatility of LH, through the decrease of hypothalamic receptor estradiol. Several factors influence the onset of puberty in sheep; among them we can mention the nutrition, the genetics, the station from birth and the social interactions. The neuropeptideo Y (NPY) this associated with the perception of the hypothalamus to the nutritional state, and it is influenced by endocrine variations, specifically in hormones as the leptin and insulin. The knowledge of these factors makes possible the anticipation of the entrance to the puberty of ewes and consequently larger profitability in the productive chain of ovine.
Keywords: Onset; Puberty; Ewes